Pengaruh Kepemimpinan, Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening pada Pegawai Pemerintah Kabupaten Ogan Komering Ilir - Transyuyan Rani Utami; Dewi Sartika (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the impact of leadership, work discipline, and work motivation on employee performance with job satisfaction as an intervening variable among employees of the Ogan Komering Ilir Regency Government. The method used is path analysis, focusing on the role of job satisfaction as a mediator between work motivation and employee performance. The results show that job satisfaction significantly mediates the effect of work motivation on employee performance. Path analysis revealed a path coefficient of 0.069 with a t-statistic of 2.121, which is higher than the t-table value of 1.97, and a P-value of 0.035, which is less than the significance level of 0.05. These findings confirm that job satisfaction mediates the relationship between work motivation and employee performance, indicating that enhancing work motivation can improve employee performance through increased job satisfaction. This study highlights the importance of motivation and job satisfaction factors in improving employee performance within the Ogan Komering Ilir Regency Government.